Rock characterization for the foundation of two water reservoirs using geophysical and borehole data - Vafidis, A.; Andronikidis, A.; Hamdan, H.; Kritikakis, G.; Economou, N.; Panagopoulos, G.; Zanettidis, S.; Merziotis, D.; Pateras, S.; Nikoforakis, E.; Blais, J. P. (Bulletin of the Geological Society of Greece, 2013)
In this work, we present the results of a geophysical survey at Malia, Crete, Greece. This survey combines VES, electrical tomography and seismic refraction at two sites where equal number of water reservoirs is planned to be constructed for the needs of a hybrid power station using wind-hydro pumping renewable energy. The geophysical sections are interpreted using geological and borehole data. This survey determines the thickness of the overburden, defines the quality of the carbonate bedrock, detects faults and weathered zones in carbonates. One major very low resistivity anomaly was detected at the northern investigated area, which corresponds to completely fractured or weathered limestone, while a 25m deep fracture zone, was detected at the southern investigated area.